LARVAL REARING OF MACROBRACillUM ROSENBERG/I (DE MAN) IN ARTIFICIAL SEA WATER - REDDY, A. K.; CHANDRA PRAKASH, CHANDRA PRAKASH; SINHA, P.S.R.K. (Journal of Indian Fisheries Association, 2015)
Larvae ofMacrobraclliumrosenbergiiwere successfully reared in artificial sea water prepared in fresh ground water.The water was circulated through a biological filter by means of air-lift pumps for a period !)f one week to remove theundissolved particles prior-to use in the hatchery operation. The experiinents w~re initiated during 1989 and the hatcheryhas been working on pilot scale since June, 1990. The larvae in all the experiments were fed with egg-custard, Moina andArtemia nauplii. The survival rate varied from 5 to 52% in the 12 experiments. These fmdings can add to the developmentof hatcheries .in the inland areas which can further boost the popularisation of giant freshwater prawn farming.